Understanding farmers' trust in stakeholders of carbon credit projects: A perception-based analysis - Mallappa, Vinaya Kumar Hebsale; Gadde, Sriharsha; Cariappa, A. G. Adeeth (Elsevier B.V., 2025)
Carbon credit projects (CCPs) are promoted to finance the adoption of carbon farming practices, yet their success depends on farmers' confidence in the organizations that recruit, train, and pay them. We investigated how farmers perceive the main actors in CCPs and which of those actors are most likely to motivate uptake of sustainable technologies. We used a perception matrix survey with 500 rice- and livestock-based farmers (the two most significant sources of agricultural emissions) in southern India to identify which actors they trust most across eight functions – participation, information, training, inclusiveness, payment transparency, understanding of farmer realities, and overall trust. State Departments of Agriculture, Horticulture, and Animal Husbandry received the highest composite score (>3.9/5), reflecting strong confidence in their technical advice, inclusive training, and fair handling of carbon credit payments. Progressive farmers and agricultural universities, including Krishi Vigyan Kendras (KVK - agricultural extension centers), formed the next tier, valued for peer demonstration and science-based support. Private companies, input dealers, and farmer-producer organizations were considered moderately reliable, while international organizations and non-governmental organizations ranked lowest due to limited village-level engagement and unclear benefits. Financial transparency emerged as the weakest function across all actors. The study underscores that public extension agencies, KVKs, and progressive farmers together constitute the trust infrastructure for credible and transparent carbon credit implementation. These findings indicate where credibility already exists and where it must be built. Embedding State Departments as nodal agencies and mandating transparent, Direct Benefit Transfer payments would institutionalize trust and accountability in future carbon projects. Project proponents can use the perception matrix framework at the design stage – and later as a diagnostic – to decide whether to deliver services through trusted public agencies and farmer networks or invest in correcting misperceptions when they stem from information gaps. Aligning CCP implementation with high-trust actors locally and publishing auditable payment schedules could accelerate the adoption of carbon farming practices, reduce disadoption, and enhance the effectiveness of India's forthcoming voluntary carbon market.